Motivated Cue-Integration and Emotion Regulation: Awareness of the Association Between Interoceptive and Exteroceptive Embodied Cues and Personal Need Creates an Emotion Goal - Shalev, Idit (Frontiers in Psychology, 2020)
Research on emotion suggests that individuals regulate their emotions to attain hedonic or instrumental goals. However, little is known of emotion regulation under low emotional clarity. The theory of motivated cue integration (MCI) suggests that emotion regulation under low emotional clarity should be understood as dissociation between a high level individual hierarchical system of goals and low level interoceptive and exteroceptive embodied cues. MCI conceptualizes low emotional clarity as the product of low access to signals of emotion that result in prediction error associated with mismatch between the current bodily state and the predicted state. This deficit in emotional processing could be understood as a problem of means substitution, suggesting that use of alternative multisensory data may facilitate situational evaluation. Based on this reasoning, a new perspective on emotion regulation under low emotional clarity is presented, according to which interchangeable attention to multisensory data associated with words, associations and images may help in cue integration, enabling the creation of a link between concrete bodily cues and abstract mental representation and a more accurate prediction. Based on the idea that emotional episodes are conceptualized as special types of goal-directed action episodes, this process will lead to the creation of broader integrative meaning, results in the development of emotion goal.